The Emerging Role of Nanomedicine in the Management of Nonalcoholic Fatty Liver Disease: A State-of-the-Art Review - Seyedeh Alia Moosavian; Thozhukat Sathyapalan; Tannaz Jamialahmadi; Amirhossein Sahebkar (Bioinorganic Chemistry and Applications)
Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease that can lead to end-stage liver disease needing a liver transplant. Many pharmacological approaches are used to reduce the disease progression in NAFLD. However, current strategies remain ineffective to reverse the progression of NAFLD completely. Employing nanoparticles as a drug delivery system has demonstrated significant potential for improving the bioavailability of drugs in the treatment of NAFLD. Various types of nanoparticles are exploited in this regard for the management of NAFLD. In this review, we cover the current therapeutic approaches to manage NAFLD and provide a review of recent up-to-date advances in the uses of nanoparticles for the treatment of NAFLD.